ACSM's introduction to exercise science - Potteiger, Jeffrey Aaron 1958-; American College of Sports Medicine (Philadelphia Wolters Kluwer, 2024)
"ACSM's Introduction to Exercise Science provides an overview of the components important to developing a solid foundation and appreciation of all aspects of exercise science. This book is designed for first-year students in exercise science or any of the related areas, including athletic training and sports medicine, clinical and sport biomechanics, clinical exercise physiology, exercise and sport nutrition, exercise physiology, exercise and sport psychology, and motor development, control, and learning. The 13 chapter topics and content were chosen to represent both the foundational and the broad-based professional areas and issues of exercise science"--
Introduction to Exercise Science -- Introduction to Research -- Exercise Science: A Systems Approach -- Exercise Physiology -- Clinical Exercise Physiology -- Athletic Training and Sports Medicine -- Exercise and Sport Nutrition -- Exercise and Sport Psychology -- Motor Behavior -- Clinical and Sport Biomechanics -- Equipment and Assessment in Exercise Science -- Careers and Professional Issues in Exercise Science -- Exercise Science in the Twenty-First Century.
Includes bibliographical references and index
Keywords: Sports Medicine; Human mechanics; Exercise -- Physiological aspects